The ordinary light microscope: an appropriate tool for provisional detection and identification of crystals in synovial fluid. Issue 12 (December 1989) - Pascual, E; Tovar, J; Ruiz, M T
Abstract : To determine if the ordinary light microscope is a useful tool in the detection and identification of crystals in synovial fluid 63 fluids (13 with monosodium urate (MSU), 14 with calcium pyrophosphate dihydrate (CPPD), one with both types of crystal, and 35 without crystals) were examined blindly by two observers, first with an ordinary light microscope, then with a polarising light microscope. Tentative identification of the crystals by their shape was attempted. The sensitivity of the ordinary light microscope for the detection of crystals was 96.2% and 100%, with specificity of 100% and 97.1% for observers 1 and 2, both with respect to the polarising light microscope. The concordance between observers for the ordinary light microscope was chi = 0.90 (0.897, 0.902) and for the polarising light microscope chi = 0.96 (0.958, 0.961). The specificity for identification of MSU and CPPD crystals by their shape with respect to the polarising light microscope was 92.3% and 85.7% for observers 1 and 2. When a polarising light microscope is not available examination of synovial fluid by an ordinary light microscope may allow a provisional diagnosis; definitive identification of the crystals requires a polarising light microscope.